Key factors influencing the success of mediation in the UK construction industry - McDonough, Andrew Francis (International Journal of Management and Sustainability, 2025)
Mediation has become an essential mechanism for resolving construction disputes, providing a time-efficient and cost-effective alternative to arbitration and litigation. This study examines the determinants of the success rate of mediation in construction projects in the UK, with particular focus on mediator competence, power relations, pre-mediation preparation, communication, and confidentiality. The study employs a quantitative methodology, with hierarchical regression analysis as the primary analytical approach to assess the impact of these determinants. Data were collected from 387 construction professionals, selected through purposive sampling, including project managers, contractors, legal advisers, and mediators. The results indicated that mediator skills are a significant determinant of effective mediation, emphasizing the importance of specialization in construction disputes. Power imbalances among disputing parties create asymmetries in projects that can undermine fairness and hinder resolution. Pre-mediation preparation and effective communication skills significantly contribute to the development of successful conflict resolution procedures. Confidentiality in complex construction ventures fosters trust, encourages open communication, and reduces adversarial opposition. These findings have practical implications for improving the mediation process through targeted training and the integration of mediation to promote fairness and efficiency. Given the limitations of a cross-sectional design, which restricts the ability to assess long-term mediation outcomes, future research could adopt longitudinal designs to explore cross-cultural variations in mediation success.